Variable Interactions between Protein Crowders and Biomolecular Solutes Are Important in Understanding Cellular Crowding - Michael Feig; Yuji Sugita (2011)
The effect of cellular crowding was examined from molecular dynamics simulations of chymotrypsin inhibitor 2 (CI2) in the presence of either lysozyme or bovine serum albumin (BSA) crowder molecules as a complement to recent experimental studies of the same systems (Miklos, A. C.; Sarkar, M.; Wang, Y.; Pielak, G. J. J. Am. Chem. Soc.2011, 133, 7116). The simulations confirm a destabilization and significantly slowed diffusion of CI2 in the presence of lysozyme and indicate that this observation is a result of extensive, nonspecific protein-protein interactions between CI2 and lysozyme. CI2 interacts much less with BSA crowders corresponding to a weak effect of crowding. Energetic analysis suggests an overall favorable crowding free energy in the presence of lysozyme, while weaker interactions with BSA appear to be unfavorable.